PENGELOLAAN PANGAN UNTUK PENANGGULANGAN BENCANA DI KABUPATEN LAMPUNG BARAT - Edwin Kastolani Burtha; Hidayat Syarief; Euis Sunarti (Jurnal Gizi dan Pangan, 2008)
Food management is important to understand to avoid food insecurity particularly during disaster. The desain of research was desk study and using secondary data which analysed descriptively at West Lampung district. Food requirement for disaster mitigation were consist of milk formula 668 kg/day, milk mush 721 kg/day, rice 33436 kg/day, noodles instant 23812 kg/day, sardines 12719 kg/day, corned beef 8919 kg/day, abon 7677 kg/day and drinking water 358638.500 ml/day. Food stock utililized for 15 days disaster emergency consist of milk formula 10020 kg, milk mush 10815 kg, rice 501540 kg, instant noodles 357180 kg, sardines 189075 kg, corned beef 133785 kg, abon 115115 kg, and drinking water 5378577500 ml. Budged required by goverment of West Lampung district for food stock at 15 days disaster emergency is Rp. 12108365000. Mechanism and mobilization of food distribution for disaster mitigation conduct by organization unit called Satlak PBP and done by operation unit called Satgas PB.